Optimization on the piezoresistivity of alkali-activated fly ash/slag mortar by using conductive aggregates and carbon fibers. (November 2020) - Ma, Yuwei; Liu, Weisen; Hu, Jie; Fu, Jiyang; Zhang, Zuhua; Wang, Hao
Abstract: Alkali-activated materials (AAMs) are regarded as an environmentally friendly alternative to ordinary Portland cement. AAMs reinforced with carbon fibers enable the piezoresistivity of materials that can sense its own strain, resistivity and damage. However, the high cost of carbon fiber limits the wide application in construction. In this study, a novel type of conductive aggregates is prepared by using porous ceramsites impregnated with modified agar and carbon black. Conductive alkali-activated fly ash/slag (AAFS) is prepared using carbon fibers and conductive ceramsites. Orthogonal experiment is applied to assess the effect of different parameters on the piezoresistivity and early age properties of AAFS mortars. The results reveal that with the combination of carbon fibers and conductive ceramsite, the electrical resistivity and piezoresistivity of AAFS are significantly improved. The good binding of ceramsites with AAFS matrix and carbon fibers ensured a high piezoresistivity of AAFS samples. A synergistic effect exists between the carbon fibers and ceramsites in view of the piezoresistivity. However, the workability and mechanical strength reduced with the addition of conductive ceramsites. AAFS mortar with 0.3% carbon fiber content, 25%–30% ceramsite content and 70% slag content is proposed as the optimal mixture in view of its mechanical properties and piezoresistivity.